Arabic validation of the Three-dimensional Meaning in Life (3DM) Scale: A bifactor model approach - Elwakeel, Sayed Ahmad; Subasi, Mustafa; Al-Hendawi, Maha; Bulut, Sefa (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2024)
Recent research provides support for the tripartite framework of meaning in life (MIL). The Three Dimensional Meaning in Life (3DM) Scale is a self-report instrument based on the tripartite framework including coherence, purpose, and significance. The present research tested the psychometric properties of the 3DM with Arabic-speaking adults. This cross-sectional study recruited a total of 516 (428 female) participants in the study through online (e.g., social media) and offline (e.g., contacting academicians at different universities in Egypt) data collection. The confirmatory factor analysis replicated the original three-factor solution to the 3DM. The factor loadings of the three-factor model from .61 to .92. The 3DM subscales had good internal consistency scores ranging from .78 to .85. The bifactor model of the Arabic 3DM did not evidence the unidimensional measurement of the 3DM. The findings demonstrate that the Arabic 3DM is a valid and reliable measure. Future research should examine different types of validity and temporal stability of the 3DM, cultural dimensions on MiL, and similarities and distinctions between the tripartite frameworks across diverse populations among Arabic-speaking people.